COVID‐19 in a human T‐cell lymphotropic virus type‐1 carrier. Issue 2 (15th February 2022) - Enomoto, Takatoshi; Shiroyama, Takayuki; Hirata, Haruhiko; Amiya, Saori; Adachi, Yuichi; Niitsu, Takayuki; Noda, Yoshimi; Hara, Reina; Fukushima, Kiyoharu; Suga, Yasuhiko; Miyake, Kotaro; Koyama, Shohei; et al.
Abstract: This is the first report of COVID‐19 in a human T‐cell lymphotropic virus type‐1 (HTLV‐1) carrier. HTLV‐1 infection can cause immune dysfunction even in asymptomatic carriers. This case highlights the need for guidance on management of COVID‐19‐HTLV‐1 coinfection, specifically on the appropriate use of corticosteroid treatment while considering secondary infection. Abstract : HTLV‐1 infection can cause immune dysfunction even in asymptomatic carriers. There is a need for guidance on how to manage COVID‐19 in patients with HTLV‐1 infection, and especially optimized steroid treatment while considering secondary infection.